Two new species in the annelid genus Stygocapitella (Orbiniida, Parergodrilidae) with comments on their biogeography - Struck, Torsten H.; Koczula, Jens; Stateczny, Dave; Meyer, Christian; Purschke, Günter (Zootaxa, 2017)
Many interstitial species with limited dispersal capacity are in fact complexes of cryptic species showing a seemingly cosmopolitan distribution. The interstitial annelid Stygocapitella subterranea (Orbiniida, Parergodrilidae) is such a complex with populations in Northern America, Europe, Australia, and New Zealand and a tropical distribution gap. Herein we present new records of Stygocapitella from South Africa, which is morphologically substantially different from S. subterranea. Additionally, using specimens from both hemispheres and morphological, nuclear and mitochondrial data as well as principal component analyses and a newly developed measurement for morphological disparity we show furthermore that the cryptic species complex of S. subterranea is not as cryptic as assumed as the Australian populations are morphologically and genetically different from the European population. Hence, we herein describe two new species, S. minuta and S. australis, within this complex from the Southern hemisphere. Additionally, we assigned a neotype for S. subterranea. This increases numbers of species known for Stygocapitella from one to three and for Parergodrilidae from two to four. Moreover, our results support an origin of this species complex on the Southern hemisphere and that both the split of S. minuta from the other two and S. subterranea from S. australis was several tens of millions years ago. Hence, the distribution of this complex was not driven by recent events, but rather it represents a strong case of decelerated morphological evolution as only slight differences in the morphology could be observed after all.